Write On! A Clinical Writing Workshop for Psychoanalysts and Psychotherapists. Issue 2 (3rd April 2021) - Naiburg, Suzi
ABSTRACT: This writing workshop is designed for new and experienced clinical writers. In it, I analyze thirteen writing samples (many from this issue) to appreciate the writer's craft. I discuss several writing terms and show how the samples illustrate them. You will also find twenty writing exercises and encouragement to find your own voice as a writer.